Analysis of Strengthening Religious and Moral Values in the Habit of Morning Pledges at Aisyiyah Bustanul Atfal Kindergarten Padang Panjang - Azzahra, Fatimah; Fauziyah, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study explores how daily habituation practices—specifically the morning pledge—can strengthen moral and religious values in early childhood. Conducted at Aisyiyah Bustanul Atfal Padang Panjang Kindergarten, it aims to demonstrate the pledge’s role in embedding core virtues such as discipline, gratitude, and belief in Allah, alongside moral qualities like respect and cooperation. Methodology: Employing a descriptive qualitative design, researchers gathered data through direct classroom observations of the morning pledge ritual, semi‑structured interviews with teachers, and review of relevant documentation (attendance records, lesson plans, and behavioral logs). This triangulated approach ensured a rich, multi‑angled understanding of how the practice is implemented and received. Results: Findings reveal that the morning pledge serves as a powerful, ritualized entry point for instilling both religious and moral values. Teachers’ active participation—leading the pledge, modeling respectful posture, and reinforcing its meanings—and their consistency in practice were identified as critical factors. Children who regularly engaged in the pledge displayed heightened awareness of discipline (arriving and standing neatly), expressed verbalized gratitude, and demonstrated cooperative behaviors during subsequent classroom activities. Applications/Originality/Value: By highlighting the pledge’s efficacy as a daily character‑building tool, this study offers a practical model for early‑childhood educators seeking to integrate value education seamlessly into routines. Its insights underscore the importance of teacher commitment and consistency and can inform teacher‑training programs and curriculum guidelines aimed at nurturing both spiritual and moral development in young learners.